2013
DOI: 10.7567/jjap.52.124101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of On-State Gate Current of AlGaN/GaN High-Electron-Mobility Transistor under Electrical and Thermal Stresses

Abstract: We have analyzed the on-state gate current of an AlGaN/GaN high-electron-mobility transistor (HEMT) by applying electrical and thermal stresses. The gate current shows a positive temperature dependence and its activation energy is less than the gate Schottky barrier height. This indicates that the gate current is a thermionic field emission and flows through a thinned AlGaN Schottky depletion layer by a tunneling or hopping mechanism. The depletion layer is considered to be thinned by the crystal defects creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Hayashi et al [8] reported a significant decrease in gate leakage current after applying a 30 min on-state stress on AlGaN/GaN HEMT. On the other hand, the changes in the other electrical characteristics were small.…”
Section: Rf Stress Results Discussion and 2d Numerical Simulationsmentioning
confidence: 99%
“…Hayashi et al [8] reported a significant decrease in gate leakage current after applying a 30 min on-state stress on AlGaN/GaN HEMT. On the other hand, the changes in the other electrical characteristics were small.…”
Section: Rf Stress Results Discussion and 2d Numerical Simulationsmentioning
confidence: 99%
“…AlGaN=GaN high-electron-mobility transistors (HEMTs) have become attractive in power electronics, microwave, and low-noise operation owing to their remarkable advantages of high breakdown field, high carrier mobility, and high saturation velocity. [1][2][3][4][5][6] Such devices have potential in space application, for which radiation effects are important issues of concern. For example, a satellite located at any near-earth orbit will be exposed to a flux of high energy particles from galaxy cosmic rays, solar flares, and Van Allen Belts, among which protons are the most common.…”
Section: Introductionmentioning
confidence: 99%